Academic literacy right from the start?: a critical realist study of the way university literacy is constructed at a Gulf university - Picard, Michelle Yvette (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2007)
The aim of this research was to examine how university literacy is constructed at a university in the Arabian Gulf and to evaluate the appropriateness of this construction where students of a low level of English are exposed to academic English (Right from the Start). Unpacking this construction is a complex task and to gain even a limited insight into the numerous Discourses, epistemologies and pedagogies constituting the construction of university literacy at Gulf universities, a stratified approach that probes the layers of 'reality' is necessary. Therefore, a critical realist approach is engaged, along with a variety of methods to probe the layers of the phenomenon. In terms of thesis organization, the traditional empirical structure common to the Social Sciences and the argumentative structure common to the Humanities are integrated. While the information obtained by a variety of methods is analysed and conclusions are reached, this material is also used along with additional literature to support the central contention that university literacy and academic English are possible 'right from the start', if the students' literacy is examined from a certain perspective and if there is an appropriate pedagogy which promotes the desired literacies. This combination of thesis structures would be deemed appropriate in the critical realist ontological framework since the rigour of the thesis lies both in its "reliability" resulting from the empirical data and its focus on the 'real'; and its "reflexivity" and "persuasivness" arising from the transparently 'critical' argument of the
Keywords: Gulf University; Education, Higher -- Persian Gulf; Literacy -- Persian Gulf; Academic writing -- Study and teaching -- Persian Gulf; English language -- Study and teaching -- Persian Gulf